If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4(x + -5) = 1 + -5(x + -3) Reorder the terms: 3x + 4(-5 + x) = 1 + -5(x + -3) 3x + (-5 * 4 + x * 4) = 1 + -5(x + -3) 3x + (-20 + 4x) = 1 + -5(x + -3) Reorder the terms: -20 + 3x + 4x = 1 + -5(x + -3) Combine like terms: 3x + 4x = 7x -20 + 7x = 1 + -5(x + -3) Reorder the terms: -20 + 7x = 1 + -5(-3 + x) -20 + 7x = 1 + (-3 * -5 + x * -5) -20 + 7x = 1 + (15 + -5x) Combine like terms: 1 + 15 = 16 -20 + 7x = 16 + -5x Solving -20 + 7x = 16 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -20 + 7x + 5x = 16 + -5x + 5x Combine like terms: 7x + 5x = 12x -20 + 12x = 16 + -5x + 5x Combine like terms: -5x + 5x = 0 -20 + 12x = 16 + 0 -20 + 12x = 16 Add '20' to each side of the equation. -20 + 20 + 12x = 16 + 20 Combine like terms: -20 + 20 = 0 0 + 12x = 16 + 20 12x = 16 + 20 Combine like terms: 16 + 20 = 36 12x = 36 Divide each side by '12'. x = 3 Simplifying x = 3
| 4m+1m=100 | | X^2+4x+4=289 | | 16q+17q=20 | | 10x-20x=30 | | 5x-6(7-2x)=10x | | 5x-3yx=-4+4y | | 3x-(7x-16)=-26 | | 9-21=3z | | -7x+33=6x+58 | | 4x-22+2x=180 | | Y=x^2-40 | | 2(5)+5=4(5)-5 | | 8x=41 | | 4x-22+2x= | | 7x+28=3x+4 | | 15+x=2 | | -6x+2y=15 | | 2+3(5j+2)=2(3j-6) | | 12w-16w=8 | | 4(8p+5)-4p=76 | | -6(r-1)=-(7r+8) | | .4x-.3=-0.14 | | 7c=c-6 | | c-33=8 | | -1.8+0.9+-1.4+0.4= | | 26-b=17 | | 9x-10=20+6x | | 18-2x=12+4x | | (3x+4y)(3x+4y)= | | c-19=13 | | 14.7xp=390 | | 2z+32=56 |